Composition for preparing dark blue light quasi-two-dimensional perovskite and application thereof
By introducing BCOEA additives into perovskite films, the high n-phase growth is inhibited and the crystallization structure is optimized, the problem of low luminescence efficiency of blue light perovskite light emitting diodes is solved, and efficient deep blue light emission and photoluminescence quantum yield is achieved. .
Patent Information
- Application Number
- CN202411355599.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-27
- Publication Date
- 2025-01-17
- Estimated Expiration
- 2044-09-27
AI Technical Summary
The existing blue light perovskite light emitting diodes have low luminous efficiency, making it difficult to achieve efficient blue light emission, and it is difficult to regulate the distribution of quasi-two-dimensional perovskite phases, resulting in poor device performance.
2-acrylic acid-2-[[(butylamino)-carbonyl]oxo]ethyl ester (BCOEA) is introduced as an additive to inhibit the overgrowth of high n-phase, optimize the crystalline structure of perovskite films, and achieve the blue-shift of spectrum and deep blue light emission to improve photoluminescence quantum yield.
The luminescence efficiency of perovskite films has been significantly improved, and the photoluminescence quantum yield has been increased to 93.4%, achieving accurate positioning and efficient emission of deep blue light areas, and broadening the application range of materials in the fields of display technology and optical communication.
Smart Images

Figure HDA0005063519400000011 
Figure HDA0005063519400000012 
Figure HDA0005063519400000013
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of electroluminescent material and device preparation, and specifically relates to a composition for preparing perovskite and a preparation method and application thereof. Background Art
[0002] Blue perovskite light-emitting diodes (PeLEDs), especially sky blue PeLEDs, are booming at an unprecedented rate. Their huge application potential in the field of commercial LED displays heralds the arrival of a technological revolution. For full-color LED displays that pursue extreme color reproduction, meeting the (0.14, 0.08) requirements in the CIE 1931 chromaticity coordinates is an indispensable part of achieving high-definition image quality. However, the blue PeLEDs currently on the market (whose CIE y values are often lower than 0.08) lag significantly behind PeLEDs in other spectral ranges in device efficiency, which has become the main bottleneck restricting their widespread application. Therefore, the development of high-efficiency deep blue perovskite films is not only a cutting-edge topic in the scientific research community, but also an urgent need to promote LED technology to a higher level. Among many candidate materials, quasi-two-dimensional perovskites have become the preferred material for preparing high-performance blue perovskite films due to their unique structure and excellent performance. Its chemical formula is L 2 (APbX 3 ) n-1 PbX 4 In the process, the change of n value flexibly regulates the number of lead halide octahedral layers, thus opening up a new way to precisely adjust the band gap and luminescence properties of the material. In the pursuit of blue light emission optimization, additive engineering has demonstrated its indispensable advantages. First, by finely regulating the n value, the band gap of the emitter can be effectively narrowed, and the precise positioning and emission of blue light can be achieved. What is particularly critical is that the complex system of quasi-two-dimensional perovskite is composed of multiple low-dimensional phases with different n values. The energy cascade transfer mechanism between these phases provides a new perspective for exploring the optimization path of blue light emission performance. By carefully controlling the distribution and content ratio of the two-dimensional phase, the non-radiative recombination loss of the excited state during the transmission process is significantly reduced, thereby significantly improving the luminescence efficiency.
[0003] Among the existing schemes, mixing halogen ions (mainly bromide ions and chloride ions) and constructing a quasi-two-dimensional perovskite structure of pure bromide ions are the two main strategies for adjusting the perovskite band gap to achieve a blue shift in the light color of perovskite materials. However, although the introduction of large steric hindrance organic ligands can construct a blue-light quasi-two-dimensional perovskite structure of pure bromide ions and achieve blue light emission from a low-dimensional phase with a wide band gap, it is very difficult to regulate the phase distribution in the quasi-two-dimensional perovskite, and it is easy to produce the coexistence of perovskite phases with different n values. In addition, the energy transfer from the low-dimensional phase to the high-dimensional phase is relatively inefficient, making it difficult for blue-light perovskite light-emitting diodes to achieve efficient blue light emission.
[0004] Therefore, there is an urgent need to develop a blue light perovskite film to solve the problem of low luminous efficiency of current blue light perovskite light-emitting diodes. Summary of the invention
[0005] The present invention aims to solve at least one of the technical problems existing in the above-mentioned prior art. To this end, the present invention proposes a composition for preparing a deep blue light quasi-two-dimensional perovskite, and the blue light perovskite film prepared therefrom significantly improves the luminous efficiency.
[0006] The present invention also provides a deep blue light quasi-two-dimensional perovskite film.
[0007] The present invention also proposes a method for preparing the deep blue light quasi-two-dimensional perovskite film.
[0008] The present invention also provides a blue light perovskite light emitting diode, which is prepared from the deep blue light quasi-two-dimensional perovskite film.
[0009] According to a first aspect of the present invention, a composition for preparing deep blue light quasi-two-dimensional perovskite is proposed, wherein the raw materials for preparing the composition include: cesium bromide, lead bromide, lead chloride and 2-acrylic acid-2-[[(butylamino)-carbonyl]oxy]ethyl ester.
[0010] The embodiments according to the first aspect of the present invention have at least the following beneficial effects:
[0011] The present invention introduces BCOEA (2-acrylic acid-2-[[(butylamino)-carbonyl]oxy]ethyl ester, CAS: 63225-53-6) as a key additive. The core of this innovative strategy is that the BCOEA additive, through its unique molecular structure and chemical properties, accurately inhibits the excessive growth of high-n phases (i.e., higher-layer perovskite phases) in quasi-two-dimensional perovskites, thereby achieving fine regulation of the optical properties of perovskite materials. Specifically, the introduction of the BCOEA additive not only promotes the crystallization optimization of perovskite films, but also significantly induces the blue shift of the spectrum, accurately blue-shifting the emission peak from the original 467nm (unmodified PL emission wavelength) to 461nm, successfully achieving precise positioning of the deep blue light region. This achievement is of milestone significance for fields such as display technology, solid-state lighting, and optical communications, as it greatly broadens the application scope of perovskite luminescent materials in color regulation. It is particularly worth mentioning that the perovskite film containing BCOEA additives not only achieves deep blue light emission, but also its photoluminescence quantum yield (PLQY) soars to an astonishing 93.4%. Compared with the perovskite film without BCOEA (PLQY is only 22.9%), this value has achieved a qualitative leap, fully demonstrating the outstanding ability of BCOEA additives in improving the luminescence efficiency of perovskite materials. High PLQY not only means that more light energy is effectively utilized, but also indicates that the material can show better performance in practical applications.
[0012] In summary, the BCOEA additive strategy of the present invention not only achieves a major breakthrough in the spectral blue shift and deep blue light emission of perovskite films, but also significantly improves the luminescence efficiency of the material.
[0013] In some embodiments of the present invention, the raw materials for preparing the composition further include: organic ligands, and the organic ligands include phenethylammonium bromide and fluorine-substituted compounds thereof and phenethylammonium chloride and fluorine-substituted compounds thereof.
[0014] In some embodiments of the present invention, the phenethylammonium bromide and the fluorine-substituted compounds thereof include at least one of phenethylammonium bromide, 2-fluorophenethylammonium bromide, 3-fluorophenethylammonium bromide and 4-fluorophenethylammonium bromide.
[0015] In some embodiments of the present invention, the phenethylammonium chloride and the fluorine-substituted compounds thereof include at least one of phenethylammonium chloride, 2-fluorophenethylammonium chloride, 3-fluorophenethylammonium chloride and 4-fluorophenethylammonium chloride.
[0016] In some embodiments of the present invention, the raw materials for preparing the composition further include: formamidine hydrobromide; and / or, the formamidine hydrobromide includes at least one of formamidine hydrobromide, methyl ammonium bromide and propyl ammonium bromide.
[0017] In some embodiments of the present invention, the raw materials for preparing the composition further include: small molecule inorganic bromide;
[0018] The small molecule inorganic bromide comprises at least one of lithium bromide, sodium bromide, zinc bromide and rubidium bromide.
[0019] In some embodiments of the present invention, the molar ratio of cesium bromide, lead bromide, lead chloride, organic ligand, formamidine hydrobromide and small molecule inorganic bromide is 1.0-1.2:x:1-x:1.1-1.3:0.1-0.3:0.1-0.3; x is 0.4-0.5.
[0020] In some embodiments of the present invention, in the composition, Pb 2+ The concentration is 0.08~0.2mmol / ml.
[0021] According to a second aspect of the present invention, a deep blue light quasi-two-dimensional perovskite film is provided, wherein the deep blue light quasi-two-dimensional perovskite film is prepared from the composition.
[0022] According to the third aspect of the present invention, a method for producing a deep blue light quasi-two-dimensional perovskite film is proposed, comprising: coating a solution of a deep blue light quasi-two-dimensional perovskite composition onto a substrate to obtain a primary film and then heating and annealing to obtain the deep blue light quasi-two-dimensional perovskite film.
[0023] In some embodiments of the present invention, the method for preparing a solution of a composition for preparing a deep blue light quasi-two-dimensional perovskite comprises: dissolving cesium bromide, lead bromide, lead chloride, organic ligands, formamidine hydrobromide, small molecule inorganic bromide and 2-acrylic acid-2-[[(butylamino)-carbonyl]oxy]ethyl ester in an organic solvent to obtain a perovskite precursor solution, and then heating the solution at 30-80°C in a nitrogen-filled glove box in a dark environment for more than 4 hours.
[0024] In some embodiments of the present invention, the amount of 2-[[(butylamino)-carbonyl]oxy]ethyl 2-acrylate added is 0.1 to 2 vol % of the perovskite precursor solution.
[0025] In some embodiments of the invention, the solvent comprises dimethyl sulfoxide.
[0026] In some embodiments of the present invention, in the perovskite precursor solution, Pb 2+ The concentration is 0.08~0.2mmol / ml.
[0027] Control Pb 2 +Concentrations within the above range help optimize the quality, performance, and stability of perovskite films.
[0028] In some embodiments of the present invention, the substrate is a pre-treated substrate.
[0029] In some embodiments of the present invention, the pre-treatment step comprises:
[0030] A1. The substrate is immersed in a cleaning solution and ultrapure water, respectively, and then the substrate is cleaned using ultrasound;
[0031] A2. Place the cleaned substrate on a hot plate or oven at 100-200°C for drying;
[0032] A3. Perform plasma cleaning on the dried substrate for 5 to 30 minutes.
[0033] In some embodiments of the present invention, the coating method comprises spin coating; the rotation speed of the spin coating is 3000 to 5000 rpm; and the time of the spin coating is 30 to 200 s.
[0034] In some embodiments of the present invention, the annealing temperature is 50-90°C.
[0035] In some embodiments of the present invention, the annealing time is 1 to 10 minutes.
[0036] In some embodiments of the present invention, the annealing time is 1 to 5 minutes.
[0037] The film exhibited the most ideal deep blue light emission characteristics during the above annealing time, and its PL peak was precisely located at 461nm. Compared with the PL peak position of 465nm when annealed for 1min, an effective blue shift to the short wavelength direction was achieved, which shows that appropriate annealing treatment can effectively promote the optimization of the internal structure of the film, reduce defects, and thus enhance the purity and efficiency of blue light emission. At the same time, appropriate annealing time can effectively promote the optimization and stabilization of the internal structure of the material, reduce non-radiative transition paths, thereby extending the relaxation time of excited state electrons and enhancing the efficiency of fluorescence radiation.
[0038] According to a fourth aspect of the present invention, a blue light perovskite light emitting diode is proposed, wherein the blue light perovskite light emitting diode is prepared from the deep blue light quasi-two-dimensional perovskite film. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] The present invention will be further described below with reference to the accompanying drawings and embodiments, wherein:
[0040] Figure 1 The photoluminescence (PL) spectra of Example 1, Example 2 and Example 3 are shown;
[0041] Figure 2PL spectra of Example 1, Comparative Example 1 and Example 4;
[0042] Figure 3 It is a transient fluorescence lifetime spectrum fitting curve diagram of Example 1, Example 2 and Example 3;
[0043] Figure 4 It is a transient fluorescence lifetime spectrum fitting curve diagram of Example 1, Comparative Example 1, and Example 4;
[0044] Figure 5 The UV-visible absorption spectra of Example 1, Comparative Example 1 and Example 4 are shown;
[0045] Figure 6 The photoluminescence quantum yield (PLQY) test graphs of Example 1, Example 2 and Example 3;
[0046] Figure 7 PLQY test diagrams of Example 1, Comparative Example 1 and Example 4. DETAILED DESCRIPTION
[0047] The words "preferably", "more preferably", etc. in the present invention refer to embodiments of the present invention that may provide certain beneficial effects in certain circumstances. However, other embodiments may also be preferred under the same circumstances or other circumstances. In addition, the description of one or more preferred embodiments does not imply that other embodiments are not applicable, nor is it intended to exclude other embodiments from the scope of the present invention.
[0048] When a numerical range is disclosed herein, the above range is considered to be continuous and includes the minimum and maximum values of the range, as well as every value between such minimum and maximum values. Further, when a range refers to an integer, every integer between the minimum and maximum values of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be combined. In other words, unless otherwise indicated, all ranges disclosed herein should be understood to include any and all subranges included therein.
[0049] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of the present invention.
[0050] Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.
[0051] Example 1
[0052] This embodiment provides a composition for preparing a deep blue light quasi-two-dimensional perovskite and a deep blue light quasi-two-dimensional perovskite film prepared therefrom, specifically:
[0053] The preparation method of the composition for preparing deep blue light quasi-two-dimensional perovskite is as follows:
[0054] A1: Cesium bromide (CsBr), lead bromide (PbBr 2 ), lead chloride (PbCl 2 ), phenethylammonium bromide (PEABr), 2-fluorophenethylammonium chloride (oF-PEACl), formamidine hydrobromide (FABr), and lithium bromide (LiBr) were mixed in a molar ratio of 1:0.5:0.5:0.6:0.6:0.15:0.15, and then 0.8 vol% of the additive material BCOEA (2-acrylic acid-2-[[(butylamino)-carbonyl]oxy]ethyl ester, CAS: 63225-53-6, the volume proportion of BCOEA in the perovskite precursor containing a solvent was 0.8%), the solvent for all materials was dimethyl sulfoxide (DMSO), and finally Pb was kept 2+ The concentration is 0.10mmol / ml. The prepared perovskite precursor solution is placed in a glove box filled with nitrogen and heated on a hot plate at 40°C in a dark environment for at least 4 hours.
[0055] The preparation method of deep blue light quasi-two-dimensional perovskite film is as follows:
[0056] S1: Soak the substrate in a cleaning solution and use ultrasonic cleaning for 60 minutes, then soak the substrate in ultrapure water and use ultrasonic cleaning for 60 minutes. During this process, the ultrapure water needs to be replaced every 20 minutes to ensure that there is no residual cleaning solution on the substrate;
[0057] S2: Place the cleaned substrate on a hot plate at 150°C for drying for no less than 5 minutes to ensure that there is no moisture on the entire substrate;
[0058] S3: The dried substrate is subjected to plasma cleaning (PLASMA) treatment for 15 min;
[0059] S4: Place the surface treated substrate into a chamber filled with inert gas (N 2 ) in a glove box, spin-coat the prepared perovskite precursor on the substrate at a spin-coating speed of 5000 rpm for 100 s. Annealing is performed immediately after the spinning is completed at a temperature of 60°C for 3 min. After cooling, a quasi-two-dimensional deep blue perovskite film is obtained.
[0060] Example 2
[0061] The present embodiment provides a composition for preparing a deep blue light quasi-two-dimensional perovskite and a deep blue light quasi-two-dimensional perovskite film prepared therefrom. The difference between this embodiment and Example 1 is that in the preparation method S4 of the deep blue light quasi-two-dimensional perovskite film, the annealing time is 1 min, and the other conditions are the same.
[0062] Example 3
[0063] The present embodiment provides a composition for preparing a deep blue light quasi-two-dimensional perovskite and a deep blue light quasi-two-dimensional perovskite film prepared therefrom. The difference between this embodiment and Example 1 is that in the preparation method S4 of the deep blue light quasi-two-dimensional perovskite film, the annealing time is 5 minutes, and the other conditions are the same.
[0064] Example 4
[0065] The present embodiment provides a composition for preparing a deep blue light quasi-two-dimensional perovskite and a deep blue light quasi-two-dimensional perovskite film prepared therefrom. The difference between this embodiment and Example 1 lies in that in the preparation method S4 of the deep blue light quasi-two-dimensional perovskite film, the content of the additive BCOEA is different, specifically: 1.6 vol% of the additive material BCOEA is added, and the other conditions are the same.
[0066] Example 5
[0067] The present embodiment provides a composition for preparing a deep blue light quasi-two-dimensional perovskite and a deep blue light quasi-two-dimensional perovskite film prepared therefrom. The difference between this embodiment and Example 1 is that in the preparation method of the composition of the deep blue light quasi-two-dimensional perovskite, phenethylammonium bromide is replaced with 2-fluorophenethylammonium bromide, and the other conditions are the same.
[0068] Example 6
[0069] This embodiment provides a composition for preparing a deep blue light quasi-two-dimensional perovskite and a deep blue light quasi-two-dimensional perovskite film prepared therefrom. The difference between this embodiment and embodiment 1 is that in the preparation method of the deep blue light quasi-two-dimensional perovskite composition, the molar ratio of 2-fluorophenethylammonium chloride is reduced, specifically, cesium bromide (CsBr), lead bromide (PbBr 2 ), lead chloride (PbCl 2 ), phenethylammonium bromide (PEABr), 2-fluorophenethylammonium chloride, formamidine hydrobromide (FABr), and lithium bromide (LiBr) are mixed in a molar ratio of 1:0.5:0.5:0.6:0.5:0.15:0.15, and the other conditions are the same.
[0070] Comparative Example 1
[0071] The present embodiment provides a composition for preparing a deep blue light quasi-two-dimensional perovskite and a deep blue light quasi-two-dimensional perovskite film prepared therefrom. The difference between this embodiment and Example 1 is that the additive BCOEA is not introduced in the preparation method of the composition of the deep blue light quasi-two-dimensional perovskite, and the other conditions are the same.
[0072] Comparative Example 2
[0073] The present embodiment provides a composition for preparing a deep blue light quasi-two-dimensional perovskite and a deep blue light quasi-two-dimensional perovskite film prepared therefrom. The difference between this embodiment and Example 1 is that N-butylcarbamic acid-2-hydroxyethyl ester (CAS: 13105-54-9) is introduced into the preparation method of the deep blue light quasi-two-dimensional perovskite composition to replace the additive BCOEA, and the other conditions are the same.
[0074] Test Case
[0075] Figure 1 The photoluminescence (PL) spectra of Example 1 (annealing for 3 minutes), Example 2 (annealing for 1 minute) and Example 3 (annealing for 5 minutes) are shown. This figure not only intuitively presents the close connection between the adjustment of annealing process parameters and the optical properties of the film, but also deeply reveals the importance of optimizing the annealing time for improving the luminescence performance of the film. It can be clearly observed from the figure that with the extension of the annealing time, the PL peak of the film undergoes a significant blue shift, but the change is not linear. Specifically, when the annealing time is set to 3 minutes, the film exhibits the most ideal deep blue light emission characteristics, and its PL peak is precisely located at 461nm, compared with the PL peak of 465nm when annealing for 1 minute, an effective blue shift to the short wavelength direction is achieved, which shows that appropriate annealing treatment can effectively promote the optimization of the internal structure of the film, reduce defects, and thus enhance the purity and efficiency of blue light emission. Furthermore, when the annealing time is extended to 5 minutes, although the blue shift trend continues, the PL peak moves to 468nm. This change may suggest that too long annealing time may introduce new structural changes or defects, which in turn have a certain adverse effect on deep blue light emission. Therefore, for this thin film system, annealing for 3 minutes is the key process parameter to achieve the best deep blue light emission performance, which is of great significance for optimizing the film preparation process and improving the performance of optoelectronic materials.
[0076] Figure 2The PL spectra of Example 1 (0.8 vol% BCOEA), Comparative Example 1 (0 vol% BCOEA), and Example 4 (1.6 vol% BCOEA) are shown. The significant effect of the concentration of BCOEA additive on the photoluminescence (PL) performance of the film is revealed. The test results show that introducing an appropriate amount of BCOEA into the film can significantly optimize its optical properties. Specifically, the film with 0.8 vol% BCOEA added exhibits the most superior PL performance, and its PL peak is precisely located at 461 nm, compared with the film without BCOEA added (PL peak is 467 nm), which achieves a significant blue shift, indicating that BCOEA as an additive can effectively adjust the band structure of the film and promote the conversion of energy to short wavelengths. What is even more remarkable is that after adding BCOEA, the PL peak intensity of the film has increased significantly, especially the film containing 0.8vol% BCOEA. Its PL intensity is not only significantly higher than that of the film without additives, but also shows a slight advantage compared with the film with a higher concentration (1.6vol%) of BCOEA. This shows that at an appropriate concentration, BCOEA can maximize its role, promoting the blue shift of the PL peak and significantly enhancing the luminescence intensity. Finally, 0.8vol% BCOEA was confirmed to be the optimal addition amount, which can ensure that the film has the highest PL intensity while achieving a significant blue shift, which has far-reaching guiding significance for the development of high-performance optoelectronic materials and devices.
[0077] Figure 3 The transient fluorescence lifetime spectrum fitting curve diagrams of Example 1 (annealing for 3 minutes), Example 2 (annealing for 1 minute) and Example 3 (annealing for 5 minutes) are shown. According to the experimental results, in Example 1 with an annealing time of 3 minutes, its fluorescence lifetime decay curve shows a more gentle downward trend compared with the embodiments with annealing for 1 minute and 5 minutes, that is, it decreases slightly slower. This phenomenon profoundly reveals the subtle effect of annealing time on the fluorescence lifetime of the material. Specifically, the film annealed for 3 minutes exhibits the longest fluorescence lifetime, which shows that appropriate annealing time can effectively promote the optimization and stabilization of the internal structure of the material, reduce non-radiative transition paths, thereby extending the relaxation time of excited state electrons and enhancing the efficiency of fluorescence radiation.
[0078] Figure 4The transient fluorescence lifetime spectrum fitting curve diagrams of Example 1 (0.8 vol% BCOEA), Comparative Example 1 (0 vol% BCOEA), and Example 4 (1.6 vol% BCOEA). According to the experimental results, the film with added BCOEA (whether 0.8 vol% or 1.6 vol%) showed significant advantages in fluorescence lifetime, and the downward trend of its decay curve was significantly more gentle, showing a fluorescence lifetime far exceeding that of the film without BCOEA added. Specifically, the introduction of BCOEA effectively slowed down the relaxation process of excited state electrons and prolonged the residence time of electrons in the excited state, thereby significantly improving the fluorescence lifetime of the film. It is worth noting that among the two films containing BCOEA additives, the film with 0.8 vol% BCOEA showed a slightly better fluorescence lifetime, which was slightly longer than that of the film with 1.6 vol% BCOEA. This subtle difference further confirms the importance of adding an appropriate amount of BCOEA for optimizing the fluorescence properties of the film. Too high or too low a concentration may not achieve the best effect.
[0079] Figure 5 The UV-visible absorption spectra of Example 1 (0.8 vol% BCOEA), Comparative Example 1 (0 vol% BCOEA), and Example 4 (1.6 vol% BCOEA) are shown in Figure 1. The experimental results show that in the n=2 phase (corresponding to a wavelength of 406 nm), all examples exhibit a clear absorption peak, and this commonality reflects the inherent optical properties of the material at this energy level. However, when the n=3 phase is reached, a striking difference emerges: compared with the film without BCOEA, the absorption intensity of the film with BCOEA added (whether at a low concentration of 0.8 vol% or a high concentration of 1.6 vol%) in the n=3 phase is significantly reduced, and even almost disappears in some cases. This significant change profoundly reveals the unique role of the BCOEA additive in regulating the optical structure of the film, which can effectively inhibit the growth or development of the n=3 phase. This inhibitory effect not only explains why the film containing BCOEA exhibits a more blue-shifted emission peak in the PL test, but also further strengthens the close connection between the emission characteristics of the film and its internal phase structure. Generally, the emission peak position of a film is dominated by its highest energy state phase, and the suppression of the n=3 phase directly leads to a blue shift of the PL spectrum, that is, the emission light moves toward higher energy (shorter wavelength).
[0080] Figure 6The photoluminescence quantum yield (PLQY) test diagrams of Example 1 (annealing for 3 minutes), Example 2 (annealing for 1 minute) and Example 3 (annealing for 5 minutes) are shown. The experimental results clearly reveal the significant effect of annealing time on the PLQY of the film. According to the experimental results, when the annealing time is 3 minutes, the PLQY of the film reaches an astonishing 93.4%. This high value indicates that under this condition, the defects inside the film are effectively passivated and the non-radiative transition pathway is significantly suppressed, thereby greatly improving the efficiency of the radiative transition and allowing more excited state energy to be released in the form of photons. In contrast, the PLQY of the film annealed for 1 minute is only 41.7%. This result reflects that the too short annealing time fails to fully promote the rearrangement of the internal structure of the film and the repair of defects, resulting in a high proportion of non-radiative transitions, thereby reducing the overall luminescence efficiency. Although the PLQY of the film annealed for 5 min increased to 61.6%, it still did not reach the optimal level, which indicates that too long annealing time may have caused some adverse factors, such as excessive grain growth or accumulation of interface stress, which to some extent offset the positive effects of annealing and limited the further improvement of PLQY.
[0081] Figure 7 The PLQY test graphs of Example 1 (0.8 vol% BCOEA), Comparative Example 1 (0 vol% BCOEA), and Example 4 (1.6 vol% BCOEA) not only reveal the significant improvement of the PLQY of the film by the BCOEA additive, but also further refine the subtle differences in the effects of different additive concentrations on performance. Specifically, when the addition amount of BCOEA is controlled at 0.8 vol%, the PLQY of the film is as high as 93.4%. This outstanding performance fully proves that the introduction of an appropriate amount of BCOEA can greatly optimize the internal structure of the film, reduce non-radiative recombination centers, and thus significantly improve the efficiency of radiative transitions, so that more excited state energy is converted into photons for radiation. However, when the addition amount of BCOEA is increased to 1.6 vol%, although the PLQY of the film remains at a relatively high level (47.3%), it has decreased significantly compared to the addition amount of 0.8 vol%. This phenomenon may mean that excessively high additive concentrations introduce new recombination pathways or defects, partially offsetting the positive contribution of BCOEA to PLQY. It is particularly noteworthy that even in the two examples with different BCOEA addition amounts, the PLQY is much higher than that of the film without BCOEA addition (22.9%). This sharp contrast strongly illustrates the key role of BCOEA additives in improving the optical properties of the film. It can not only significantly improve PLQY, but also reveal the possibility of further optimizing performance by adjusting the concentration of additives.
[0082] The deep blue light quasi-two-dimensional perovskite film obtained in Comparative Example 2 cannot effectively suppress the formation of internal defects in the material due to N-butylcarbamic acid-2-hydroxyethyl ester, and its photoluminescence quantum yield (PLQY) is expected to decrease. In addition, compared with Comparative Example 2, the design of the BCOEA molecule cleverly incorporates longer chain length features, which not only enriches the diversity of its chemical structure, but also brings significant changes in physical properties. Specifically, the extended chain length enables the BCOEA molecule to form a more extensive and stable hydrogen bond network when interacting with organic ligands. This enhanced hydrogen bonding effect not only increases the steric hindrance, effectively preventing the disordered aggregation between molecules, but also promotes the ordering of the internal structure of the material, achieving better phase splitting. The optimization of phase splitting directly promotes the concentrated transmission of energy inside the material, constructs an efficient "energy funnel" system, and enables photogenerated carriers to be more smoothly guided to specific areas for recombination, thereby greatly improving the photoelectric conversion efficiency and device performance.
[0083] The above content describes the embodiments of the present invention in detail, but the present invention is not limited to the above embodiments. Various changes can be made within the knowledge of ordinary technicians in the relevant technical field without departing from the purpose of the present invention. In addition, the embodiments of the present invention and the features in the embodiments can be combined with each other without conflict.
Claims
1. A composition for preparing deep blue light quasi-two-dimensional perovskite, characterized in that: The raw materials for preparing the composition include: cesium bromide, lead bromide, lead chloride and 2-acrylic acid-2-[[(butylamino)-carbonyl]oxy]ethyl ester.
2. The composition according to claim 1, characterized in that The raw materials for preparing the composition also include: organic ligands, and the organic ligands include phenethylammonium bromide and fluorine-substituted compounds thereof and phenethylammonium chloride and fluorine-substituted compounds thereof.
3. The composition according to claim 2, characterized in that The phenethylammonium bromide and fluorine-substituted compounds thereof include at least one of phenethylammonium bromide, 2-fluorophenethylammonium bromide, 3-fluorophenethylammonium bromide and 4-fluorophenethylammonium bromide.
4. The composition according to claim 2, characterized in that The phenethylammonium chloride and fluorine-substituted compounds thereof include at least one of phenethylammonium chloride, 2-fluorophenethylammonium chloride, 3-fluorophenethylammonium chloride and 4-fluorophenethylammonium chloride.
5. The composition according to claim 1, characterized in that The raw materials for preparing the composition further include: formamidine hydrobromide; and / or the formamidine hydrobromide includes at least one of formamidine hydrobromide, methyl ammonium bromide and propyl ammonium bromide.
6. The composition according to claim 1, characterized in that The raw materials for preparing the composition also include: small molecule inorganic bromide; the small molecule inorganic bromide includes: at least one of lithium bromide, sodium bromide, zinc bromide and rubidium bromide.
7. The composition according to claim 1, characterized in that In the solution state, in the composition, Pb 2+ The concentration is 0.08~0.2mmol / ml.
8. A deep blue light quasi-two-dimensional perovskite film, characterized in that: The deep blue light quasi-two-dimensional perovskite film is prepared from the composition described in any one of claims 1 to 7.
9. A method for preparing the deep blue light quasi-two-dimensional perovskite film according to claim 8, characterized in that: include: A solution of a deep blue light quasi-two-dimensional perovskite composition is coated on a substrate to obtain a primary film, which is then heated and annealed to obtain the deep blue light quasi-two-dimensional perovskite film.
10. A blue perovskite light-emitting diode, characterized in that: The blue light perovskite light-emitting diode is prepared from the deep blue light quasi-two-dimensional perovskite film described in claim 8.
Citation Information
Patent Citations
Low-pressure-resistant quantum dot ink and preparation method thereof, color film and display device
CN117467308A
Dark blue light perovskite light-emitting diode and preparation method thereof
CN117794330A
Bilateral amines for defect passivation and surface protection in perovskite solar cells
US20220025195A1